2002
DOI: 10.1111/1475-3995.00375
|View full text |Cite
|
Sign up to set email alerts
|

Multi–objective Evolutionary Algorithms for the Risk–return Trade–off in Bank Loan Management

Abstract: Multi-criteria decision-making is an increasingly accepted tool for decision-making in management. In this work, we highlight the application of a novel multi-objective evolutionary algorithm, NSGA-II, to the risk-return tradeoff for a bank-loan portfolio manager. The manager of a bank operating in a competitive environment faces the standard goal of maximizing shareholder wealth. Specifically, this attempts to maximize the net worth of the bank, which in turn involves maximizing the net interest margin of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(32 citation statements)
references
References 17 publications
0
32
0
Order By: Relevance
“…There exists some disconnected spaces on Pareto front in Fig.3. The Pareto front consists of 3,5], and x * 2 = 3. For case 2, constraint conditions are also two inequality statement.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…There exists some disconnected spaces on Pareto front in Fig.3. The Pareto front consists of 3,5], and x * 2 = 3. For case 2, constraint conditions are also two inequality statement.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The fuzzy multi-attribute decision-making (MADM) method has been used to support the decisionmaking process in sustainable housing (Li and Shen 2002). Mukerjee (2002) used a multi-objective decisionmaking method to solve optimisation problems in riskreturn trade-off in bank loan management.…”
Section: Fuzzy Sets Approach In Decision Makingmentioning
confidence: 99%
“…They demonstrated that in this case, the selection of the portfolios becomes more complicated because the problem model has to manage mixed integer variables and nonlinear objectives. From a more general point of view, Mukerjee et al [20] utilize NSGA-II to implement a decision-making multicriteria model used in the risk/performance negotiation by a bank loan manager. Two models with respect to this negotiation were considered.…”
Section: Related Workmentioning
confidence: 99%